Recommended methods for purification of solvents and tests for impurities - Coetzee, Johannes Francois (Pergamon Press, 1982)
Recommended Methods for Purification of Solvents and Tests for Impurities is a compilation of recommended procedures for purification of solvents and tests for solvent impurities. Ten solvents are covered: acetonitrile, sulfolane, propylene carbonate, dimethyl sulfoxide, dimethylformamide, hexamethylphosphoramide, pyridine, ethylenediamine, N-methylacetamide, and N-methylpropionamide. This book is comprised of 12 chapters and opens with an introduction to general aspects of impurity effects. The rationale for the selection of solvent is explained, and the relative reactivities of solutes in di.